2017
DOI: 10.1155/2017/6287156
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Spatially Variable Effects of Climate Change on Rice Yield for Three Ecotypes in Bangladesh, 1981–2010

Abstract: Climate change will impact on rice food security in many parts of the world, including Bangladesh. Little attention has been given to understanding the impact of climate on rice yield for three main ecotypes (Aus, Aman, and Boro) in different areas of the country. The aim of this paper was to analyse the spatiotemporal dynamics of rice yield and climatic variables and the spatially variable climate effects on rice yield for these ecotypes in Bangladesh during 1981-2010 by employing linear mixed models and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In another study, Ara et al (2016) observed that rice yields in Bangladesh are negatively impacted by rising temperatures and increased rainfall. Similarly, Ara et al (2017) showed that yields for three main types of rice produced in Bangladesh are more susceptible to changes in temperature than they are to changes in rainfall. Although the impact of climate change on different types of rice is asymmetric, the Boro type is likely to be more resilient to climate change than the Aus or Aman types.…”
Section: Literature Reviewmentioning
confidence: 98%
“…In another study, Ara et al (2016) observed that rice yields in Bangladesh are negatively impacted by rising temperatures and increased rainfall. Similarly, Ara et al (2017) showed that yields for three main types of rice produced in Bangladesh are more susceptible to changes in temperature than they are to changes in rainfall. Although the impact of climate change on different types of rice is asymmetric, the Boro type is likely to be more resilient to climate change than the Aus or Aman types.…”
Section: Literature Reviewmentioning
confidence: 98%
“…This is because aman season rice is grown in all field types (i.e., different landscape positions), often with different varieties and varying amounts of inputs. Other studies have reported large spatiotemporal variation for rice yield in smallholder systems of Bangladesh, even under the same varieties and fertilizer inputs (Ara et al 2017 ; Assefa et al 2021 ). In southern Bangladesh, variation in soil fertility (mostly nitrogen) and field elevation (which controls flooding depth) are important determinants of rice yield (Ara et al 2017 ; Ran et al 2018 ).…”
Section: Discussionmentioning
confidence: 95%
“…6b). Although the spatial variations in long-term temperature are small, the differences may influence food security across the country in the long term and are similar in magnitude to the climate changes predicted to occur during the next decades (Ara et al 2016(Ara et al , 2017.…”
Section: Food Security and Climate Change In Bangladeshmentioning
confidence: 93%
“…Bangladesh is facing challenges in attaining and maintaining food security because of its large population, numbering 152 million at the last population census from 2011 (BBS 2011a). In addition, numerous drivers including poverty (Kam et al 2005), malnutrition (Bose and Dey 2007; Hossain et al 2005), frequent disasters (Mirza 2002;Ninno and Lundberg 2005), agricultural management practices (Ara et al 2016) and the effect of climate change (Karim et al 1996;Sarker et al 2012;Ruane et al 2013;Ara et al 2017) influence food security across the country (Habiba et al 2015a). …”
Section: Introductionmentioning
confidence: 99%